Ecological niche modeling approach for assessing potential for expansion of irrigated rice under alternate wetting and drying method in Burkina Faso - CGIAR Research Program on Rice (2020)
The evaluation metrics such as the area under the curve and percentage correctly classified showed values higher than 80% for both RF and MaxEnt. The modeling approach is validated for Burkina Faso and can be applied to the whole West African region.